Political Dynasties in Democratic Contexts: A Comprehensive Bibliometric Analysis Using Scopus Data - Taufiq, Muhammad; Adilansyah, Adilansyah; Hidayat, Rahmad (Thammasat Review, 2025)
This article examines the phenomenon of political dynasties in the context of democracy through a comprehensive bibliometric analysis using data from Scopus. By reviewing 143 documents published between December 2009 and June 2024, the authors identify trends, key topics, and remarkable contributions to the study of political dynasties. The data includes 116 journal articles, five books, six book chapters, one conference paper, one note, and fourteen reviews. Annual scientific output mapping reveals the influence of prior studies over time, and the geographical research distribution tracking confirms diverse focuses across countries. Popular topics and thematic developments in political dynasty studies are outlined thoroughly, reflecting key issues and changes in political, social, and economic contexts. The analysis offers a complete overview of the political dynasty research landscape, facilitating the identification of trends, key contributions, and areas that require further research. The results are significant for understanding the dynamics of political dynasties in the context of democracy and their implications for the democratization process, political stability, and economic development.